RPIM Policy and MSME Financing: Evidence from Indonesian Islamic Banks - Salma Darapuspita; Resfa Fitri; M. Nur Faaiz F Achsani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to evaluate the impact of the Macroprudential Inclusive Financing Ratio (RPIM) policy on the financing behavior and inclusivity performance of Islamic Commercial Banks (BUS) in Indonesia, particularly in supporting the 30% MSME financing target mandated by Bank Indonesia. Using a quantitative approach with quarterly time-series data from 2016Q1 to 2024Q4 sourced from OJK, Bank Indonesia, BPS, the World Bank, and WHO, the study applies the Autoregressive Distributed Lag (ARDL) model to analyze short-run and long-run relationships between MSME financing and several determinants, including bank-specific factors (FDR, NPF, ROA), macroeconomic indicators (GDP, inflation, BI Rate), and policy dummies representing RPIM implementation and the COVID-19 pandemic. The results reveal that the RPIM policy has a positive effect on total MSME financing but does not significantly increase its proportion relative to total financing. The policy’s impact is more evident in working capital financing than in investment financing, suggesting that Islamic banks tend to expand short-term, liquidity-oriented MSME loans rather than long-term investments. These findings imply that while the RPIM policy has improved financing volumes, achieving structural inclusivity requires enhanced policy incentives and risk-sharing mechanisms to encourage long-term MSME investment. This study contributes to the literature by providing empirical evidence on the early effectiveness of the RPIM policy in Indonesia’s Islamic banking sector and offering policy insights for strengthening inclusive and sustainable financing.